Análisis y diseño de un sistema de gestión de seguridad de la información sobre la base de las normas ISO 27001 y 27002 para la Superintendencia de Control del Poder de Mercado - Landeta Guachamin, Fabiola Lorena (2016)
Entities are threatened daily by risks that endanger the integrity, confidentiality, availability of the information and technology that hold it up, this may affect the business continuity. The current titling project is focused on the design of a Security Management System of the Information for the Superintendence of Market power´s control according to the stardard established by the international rule ISO/IEC 27001:2005. The rule ISO/IEC 27001.2005 is used as a guide for the development of the SGSI to analize, define and design standars which can be applied within the entity so it can have an important progress and also the accomplishment of a regulatory rule (Deal 166) applying technical norms and effective safety practices, through this its allowed to recommend appropiate measures which can be applied within the entity for the management against potential risk that can affect the information´s safety. Finally as a result a propose is made with guidelines and good practices of security according to the entity’s necesity.